MORPHOLOGICAL STRUCTURE AND ELEMENTAL COMPOSITION ANALYSIS OF THE DMK+FK IONITE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
In recent years, the development of effective sorbent materials to ensure environmental safety and reduce industrial waste has become a pressing issue. Ion- exchange resins with high sorption properties play an important role, especially in the separation and recovery of metal ions. In this study, an ionite compound based on dimethylcarbamoyl (DMK) and a phosphorus-containing component (FK) was synthesized, and its surface morphology and elemental composition were investigated using scanning electron microscope